TINJAUAN YURIDIS PERATURAN DAERAH KABUPATEN KUTAI BARAT NOMOR 13 TAHUN 2017 TENTANG PENYELENGGARAAN PENGAKUAN DAN PERLINDUNGAN MASYARAKAT HUKUM ADAT TERHADAP HUKUM NASIONAL - Ratna Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACT Customary law or what can also be called customary law is a law that grows and lives in a community that aims to regulate the way of life of the community. Customary law that adheres to noble values and norms that has been passed down from generation to generation, which has survived and until now has an important role in the national legal order.The state recognizes the existence of Costomary law by including several articles regulating customary law in the 1945 Constitution of the State of the Republic of Indonesia and then relegating it in its derivative products to regional regulations.The problem raised in the writing of this law is how the position of  Customary law in West Kutai District Regulation Number 13 Year 2017 Regarding the Implementation of the Recognition and Protection of Traditional Law Communities and what matters are regulated in these regional regulations that affect the enactment of Adat law in Kutai Regency West. This type of research is normative juridical research, library research with the problem approach used in writing this thesis is the statute approach.The birth of West Kutai Regency Regulation Number 13 Year 2017 Regarding the Implementation of the Recognition and Protection of Customary Law Communities is a form of local government support for the development and existence of customary law in West Kutai Regency to date as part of the national legal system. Keywords: customary law, regional regulations, national law